m6A methylation: Critical roles in aging and neurological diseases - Fan, Yishu; Lv, Xinyi; Chen, Zhuohui; Peng, Yanyi; Zhang, Mengqi (Frontiers in Molecular Neuroscience, 2023)
N6-methyladenosine (m6A) is the most abundant internal RNA modification in eukaryotic cells, which participates in the functional regulation of various biological processes. It regulates the expression of targeted genes by affecting RNA translocation, alternative splicing, maturation, stability, and degradation. As recent evidence shows, of all organs, brain has the highest abundance of m6A methylation of RNAs, which indicates its regulating role in central nervous system (CNS) development and the remodeling of the cerebrovascular system. Recent studies have shown that altered m6A levels are crucial in the aging process and the onset and progression of age-related diseases. Considering that the incidence of cerebrovascular and degenerative neurologic diseases increase with aging, the importance of m6A in neurological manifestations cannot be ignored. In this manuscript, we focus on the role of m6A methylation in aging and neurological manifestations, hoping to provide a new direction for the molecular mechanism and novel therapeutic targets.